Role of immersive virtual reality in motor behaviour decision-making in chronic pain patients - Guerra-Armas, Javier; Flores Cortés, Mar; Pineda-Galán, Consolación; Luque-Suárez, Alejandro; La Touche, Roy (MDPI, 2023)
Primary chronic pain is a major contributor to disability worldwide, with an estimated prevalence of 20–33% of the world’s population. The high socio-economic impact of musculoskeletal pain justifies seeking an appropriate therapeutic strategy. Immersive virtual reality (VR) has been proposed as a first-line intervention for chronic musculoskeletal pain. However, the growing literature has not been accompanied by substantial progress in understanding how VR exerts its impact on the pain experience and what neurophysiological mechanisms might be involved in the clinical effectiveness of virtual reality interventions in chronic pain patients. The aim of this review is: (i) to establish the state of the art on the effects of VR on patients with chronic pain; (ii) to identify neuroplastic changes associated with chronic pain that may be targeted by VR intervention; and (iii) to propose a hypothesis on how immersive virtual reality could modify motor behavioral decision-making through an interactive experience in patients with chronic pain.
Keywords: Dolor - Tratamiento; Realidad virtual - Uso terapéutico; Enfermedades crónicas - Tratamiento; Trastornos motores - Tratamiento; Virtual reality; Body embodiment; Motor behavior; Chronic pain; Decision-making